The earliest giant Osprioneides borings from the Sandbian (late ordovician) of Estonia. - Olev Vinn (Public Library of Science (PLoS), 2014)
The earliest Osprioneides kampto borings were found in bryozoan colonies of Sandbian age from northern Estonia (Baltica). The Ordovician was a time of great increase in the quantities of hard substrate removed by single trace makers. Increased predation pressure was most likely the driving force behind the infaunalization of larger invertebrates such as the Osprioneides trace makers in the Ordovician. It is possible that the Osprioneides borer originated in Baltica or in other paleocontinents outside of North America.